Genetic structuring of Ephedra an important medicinal plant from low to high altitudinal zones of Balochistan, Pakistan - Abdul Basit; Shazia Saeed; Alia Ahmed; Nizam Baloch; Asif Zahid Ali (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Basit A, Saeed S, Ahmed A, Baloch N, Ali AZ. 2021. Genetic structuring of Ephedra an important medicinal plant from low to high altitudinal zones of Balochistan, Pakistan. Biodiversitas 22: 713-718. The current study is based on the genetic structuring of three Ephedra species compared to the morphological and phytochemical investigation. Ephedra is a significant, medicinally important genus growing naturally in arid and semi-arid regions of Balochistan Pakistan. Resolving the taxonomic identification of Ephedra species genetic variability was estimated by using Random Amplified Polymorphic DNA and Inter-Simple Sequence Repeats. Higher values revealed that E. foliata possess high genetic diversity. Less diversity was observed within Takatu Mountain Range population. Diversity in Nushki region was found higher than the Takatu Mountain Range. The genetic diversity was maintained within the populations of all three species of Ephedra at Hazarganji-Chiltan National Park. That may be due to the less anthropogenic activity in conserved region of the Park. Assessment and conservation of genetic diversity through molecular markers is essential that could be used as a key to conserve genetic variability. This study is the first endeavor to estimate genetic and phytochemical diversity within and among diverse populations of Ephedra from the region to the best of our knowledge. Genetic diversity can be used as key tool for further development of a management plan for ex situ reproduction and in situ conservation